HIV-1 Nef compensates for disorganization of the immunological synapse by inducing trans-golgi network-associated Lck signaling - Pan, Xiaoyu; Rudolph, Jochen M.; Abraham, Libin; Habermann, Anja; Haller, Claudia; Krijnse-Locker, Jacomine; Fackler, Oliver Till (Blood, 2012)
The Nef protein of HIV-1 facilitates viral replication and disease progression in vivo. Nef disturbs the organization of immunological synapses between infected CD4+ T lymphocytes and antigen-presenting B-lymphocytes to interfere with TCR proximal signaling. Paradoxically, Nef enhances distal TCR signaling in infected CD4+ T lymphocytes, an effect thought to be involved in its role in AIDS pathogenesis. Using quantitative confocal microscopy and cell fractionation of Nef-expressing cells and HIV-1-infected primary human T lymphocytes, we found that Nef induces intracellular compartmentalization of TCR signaling to adjust TCR responses to antigenic stimulation. Nef reroutes kinase-active pools of the TCR signaling master switch Lck away from the plasma membrane (PM) to the trans-Golgi network (TGN), thereby preventing the recruitment of active Lck to the immunological synapse after TCR engagement and limiting signal initiation at the PM. Instead, Nef triggers Lck-dependent activation of TGN-associated Ras-Erk signaling to promote the production of the T lymphocyte survival factor IL-2 and to enhance virus spread. Overexpression of the Lck PM transporter Unc119 restores Nef-induced subversions of Lck trafficking and TCR signaling. Nef therefore hijacks Lck sorting to selectively activate TGN-associated arms of compartmentalized TCR signaling. By tailoring T-lymphocyte responses to antigenic stimulation, Nef optimizes the environment for HIV-1 replication.